2018
DOI: 10.1192/bjp.2018.87
|View full text |Cite
|
Sign up to set email alerts
|

Remission of depression in patients with schizophrenia and comorbid major depressive disorder: results from the FACE-SZ cohort

Abstract: Antidepressant administration is associated with lower depressive symptom level in patients with schizophrenia and MDD. Paranoid delusions and alcohol misuse disorder should be specifically explored and treated in cases of non-remission under treatment. MetS may play a role in MDD onset and/or maintenance in patients with schizophrenia.Declaration of interestNone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 52 publications
2
35
1
Order By: Relevance
“…As suggested by Figure 4, treatment with fluoxetine or risperidone effectively relieves the typical symptoms of depression or schizophrenia, whereas the combined drug application cannot relieve the helplessness or anhedonia symptoms in the MK801 + CUMS model. Such observations in mouse models largely agree with clinical observations showing the minimal alleviation of depressive symptoms by antidepressant treatment in schizophrenia patients complicated with depressive disorders (Fond et al, 2018). This behavioral observation is further substantiated by the analysis of neuronal recordings showing that the impaired neuronal activity in the PFC cannot be relieved by the combined antipsychotic and antidepressant treatment.…”
Section: Discussionsupporting
confidence: 84%
“…As suggested by Figure 4, treatment with fluoxetine or risperidone effectively relieves the typical symptoms of depression or schizophrenia, whereas the combined drug application cannot relieve the helplessness or anhedonia symptoms in the MK801 + CUMS model. Such observations in mouse models largely agree with clinical observations showing the minimal alleviation of depressive symptoms by antidepressant treatment in schizophrenia patients complicated with depressive disorders (Fond et al, 2018). This behavioral observation is further substantiated by the analysis of neuronal recordings showing that the impaired neuronal activity in the PFC cannot be relieved by the combined antipsychotic and antidepressant treatment.…”
Section: Discussionsupporting
confidence: 84%
“…Due to the cross-sectional retrospective design, no causal association may be drawn from the present findings and further clinical trials are also needed to determine if vitamin D supplementation in patients with hypovitaminosis D may definitely improve depression and anxiety. Treating depression in schizophrenia remain a challenge in the current state of the art (Guillaume Fond et al, 2018), and vitamin D may be suggested as a low-cost and high benefit/risk ratio add-on therapy in SZ patients with depressive and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The screening for depression and anxiety in SZ is rarely carried out. One explanation is the debate of the existence of major depression and anxiety disorders as comorbidities of schizophrenia (Guillaume Fond et al, 2018). Some authors suggest that anxiety and depressive symptoms are part of psychotic symptomatology (as measured by the PANSS depressive factor that includes anxiety and depressive symptoms) (Wallwork et al, 2012).…”
Section: No Association Between Positive and Negative Symptoms And Hymentioning
confidence: 99%
See 2 more Smart Citations